The reshaping during construction of the right abutment foundation of the New Alto Ceira Dam in Portugal - Cunha, J. (2012)
The New Alto Ceira Dam is a 41 m high and 133 m long at the crest concrete arch dam, located in the middle zone of Portugal. The objective of the dam’s construction is to replace the existing dam located about 200 m upstream, which is highly deteriorated due to swelling phenomena. The New dam’s foundation lies over sound schists, in which some sets of discontinuities can be observed. During the dam construction, two expressive rock discontinuities (one on each bank), that could cause problems to the dam-foundation safety, were identified, leading to additional studies of foundation failures scenarios. The discontinuity in the right bank was parallel to the right abutment surface and about 3 m deep. Under these conditions, the foundation of the abutment was redesigned. The 3DEC (3-Dimensional Distinct Element Code) was used to simulate the potential failure mechanisms defined by the natural rock discontinuities and the concrete-rock interface in order to evaluate the safety and effectiveness of the proposed foundation design. The numerical model represents the geological structure of the rock mass, the concrete vault with its contraction joints and foundation surface. The actions of the dead weight, reservoir water pressure, uplift pressures and water pressures in rock were taken into account. The safety analysis was performed by progressive reduction of strength along the discontinuities until the failure condition was reached, and the safety of the right abutment for the new deeper surface foundation could be proved.